Prophylactic Bracing Has No Effect on Lower Extremity Alignment or Functional Performance - Hueber, Garrett A.; Hall, Emily A.; Sage, Brad W.; Docherty, Carrie L. (International Journal of Sports Medicine, 2017)
Prophylactic ankle bracing is commonly used during physical activity. Understanding how bracing affects body mechanics is critically important when discussing both injury prevention and sport performance. The purpose is to determine if ankle bracing affects lower extremity mechanics during the Landing Error Scoring System test (LESS) and Sage Sway Index (SSI). Thirty physically active participants volunteered for this study. Participants completed the LESS and SSI in both a braced and unsupported conditions. Total errors were recorded for the LESS. Total errors and time (seconds) were recorded for the SSI. The Wilcoxon signed-rank test was utilized to evaluate any differences between the brace conditions for each dependent variable. A priori alpha level was set at p<0.05. The Wilcoxon signed-rank test yielded no significant difference between the braced and unsupported conditions for the LESS (Z=−0.35, p=0.72), SSI time (Z=−0.36, p=0.72), or SSI Errors (Z=−0.37, p=0.71). Ankle braces had no effect on subjective clinical assessments of lower extremity alignment or postural stability. Utilization of a prophylactic support at the ankle did not substantially alter the proximal components of the lower kinetic chain.
Keywords: ankle; landing error scoring system; external support